PENGARUH KEPEMIMPINAN DAN MUTASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. ARVENA SEPAKAT KABUPATEN INDRAGIRI HULU - Abdul Hairudin (JURNAL MANAJEMEN DAN BISNIS, 2018)
The purpose of this study was to determine the effect of leadership and work mutations on employee job satisfaction. The study was conducted with quantitative methods, namely research that describes the influence of leadership and work mutations on employee job satisfaction at PT. Arvena Sepakat Indragiri Hulu. By analyzing the data using multiple regression, correlation coefficients, and hypothesis testing which will later be assisted by using SPSS version 21. From the results of the study with the regression equation Y = 0.744 + 1.386 X1 + 0.892 X2. a = constant of 0.744 means that employee job satisfaction is 0.744 if X1 (leadership) and X2 (work mutation) are equal to 0 (zero). b1 = leadership regression coefficient of 1.386 shows that every increase in leadership by one unit and other variables (work mutations) remain, then there will be an increase in employee job satisfaction of 1.386. b2 = regression coefficient of work mutation of 0.892 shows that every increase in work mutations by one unit and other variables (leadership) remains, then there will be an increase in employee job satisfaction of 0.892. The correlation coefficient is known that R is 0.826 meaning that it has a very strong and unidirectional relationship. and then tested with the multiple determination coefficient (R2) is 0.682. this shows that (X1) leadership and (X2) work mutations together can contribute to the variable (Y) employee job satisfaction of 68.2%. And the remaining 31.8% is contributed by other variables. Hypothesis testing on a significant level = 5% where F arithmetic (83.702)> F table (3.11) then Ho is rejected and Ha is accepted. This means that leadership variables and work mutations together have a significant influence on employee job satisfaction at PT. Arvena Sepakat Indragiri Hulu, and based on a partial test where t counts (5,786)> from t table (1,990), then Ho is rejected by Ha, it means that leadership has a significant influence on employee job satisfaction and t count (3,665)> than t table (1,990) then Ho is rejected and Ha is accepted, which means work mutation has a significant influence on employee job satisfaction.